Using Machine Learning to Predict the Stock Market Trend - Chen, Pengyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
For a long time, people have been trying to predict the direction of stocks, employing various methods. This paper explores the application of machine learning algorithms in predicting stock market trends, aiming to address the challenges of traditional methods and leverage the advantages of data-driven approaches. Highlights the limitations of conventional techniques and elucidates the potential of machine learning in capturing complex market dynamics. This paper discusses various machine learning algorithms and their characteristics, emphasizing their adaptability and scalability in analyzing vast amounts of data. Through empirical analysis and comparative evaluations, this paper demonstrates the efficacy of machine learning in enhancing prediction accuracy and informing investment decisions. This paper explores using machine learning for stock market prediction, overcoming traditional limitations and leveraging data-driven approaches. It discusses various algorithms, showing their adaptability and scalability, and demonstrates their efficacy in enhancing prediction accuracy. Our study contributes to the growing body of research on stock price prediction by leveraging advanced computational techniques to maneuver through the ever-changing financial markets.